The Ghanaian Perspective of Attitudes towards Francophones Learning English as a Second Language - Vera Gyamera; Fauna Frimpong (FOSTER: Journal of English Language Teaching, 2024)
The study investigates the attitudes of Francophone students learning English as a Second Language (ESL) at the Ghana Institute of Languages (GIL), focusing on the influence of gender and age. Using a quantitative approach, the research surveyed 267 students from various Francophone countries through questionnaires. Statistical analysis, including descriptive statistics and ANOVA, revealed that students generally hold positive attitudes toward learning English. Female students demonstrated significantly more favorable attitudes (M = 4.46, SD = 0.36) than their male counterparts (M = 4.21, SD = 0.77), while age showed a negative correlation with attitudes. Younger students (16–20 years) exhibited the most positive attitudes (M = 4.39, SD = 0.45), which declined in older groups. These findings highlight gender and age as critical factors in shaping attitudes toward second language learning. The study underscores the importance of attitudinal factors in ESL acquisition, offering practical and theoretical insights for policymakers and educators. It calls for targeted interventions to sustain positive attitudes across demographic groups and further research incorporating qualitative methods to explore factors like anxiety and cultural adaptation. The findings contribute to the growing body of literature on language attitudes, particularly within multilingual African contexts.